PERAN BADAN NARKOTIKA NASIONAL DALAM PENANGULANGAN PENYALAHGUNAAN NARKOTIKA DI KOTA SUKABUMI - Farhani, Nabila Ulayya Rizkya (Program Studi Hukum, Universitas Muhammadiyah Sukabumi, 2025)
Narcotics abuse in Indonesia is increasingly worrying. To optimize the prevention and eradication of this problem, the National Narcotics Agency (BNN) was established through Law Number 35 of 2009. BNN is tasked with preventing and eradicating the abuse and illicit circulation of narcotics effectively. This study aims to analyze the implementation of countermeasures for narcotics abuse by the National Narcotics Agency in Sukabumi City, as well as identify supporting and inhibiting factors in these efforts. The methodology employed draws on criminal policy theory and legal system theory. The results of the study show that BNN has an important role in preventing and eradicating narcotics trafficking. However, challenges still exist, such as a lack of resources and community support. The suggestion for BNN is to increase collaboration with local communities and related agencies, as well as strengthen education programs to increase public awareness about the dangers of narcotics. With these measures, it is hoped that narcotics abuse in the city of Sukabumi can be minimized and similar problems will not occur in the future. .